Successful turnarounds in bankrupt firms? Assessing retrenchment in the most severe form of crisis - Manuel Rico; Francisco Puig (BRQ Business Research Quarterly, 2021)
During economic downturns, firms file for bankruptcy in an effort to attempt a "turnaround". The objective of this study is to assess the effectiveness of retrenchment strategies in the context of bankruptcy, as the most severe form of crisis. We conducted a longitudinal analysis of a sample of 868 bankrupt Spanish firms during the period 2004-2017. The empirical results show that stakeholder support and deep cost retrenchment increase the likelihood of survival and performance recovery, while aggressive layoffs are detrimental for turning bankrupt firms around. Surprisingly, intense asset retrenchment had no significant effects on firm survival and also pushed performance downward. The findings suggest that retrenchment should not be regarded as a general remedy for firms suffering the most severe of crisis. Bankrupt firms should focus on restoring stakeholder relationships and reducing superfluous expenses, while making employees redundant or selling assets should be evaluated carefully when attempting a turnaround.
Keywords: M10; G33; 650; stakeholders; decline; retrenchment; Spain; strategy; Turnaround